Participação social na gestão municipal da segurança pública : analisando o conselho municipal de justiça e segurança de Porto Alegre - Xavier, Maralice Fernandes (2017)
This study addresses the social participation in the Municipal Public Security Management: Analyzing the Municipal Council of Justice and Security of Porto Alegre. It has a relevant impact on the lives of citizens and one of the objectives proposed here refers to the extent to which this social participation can contribute to the debate and discussion of the management of public safety policies in the city of Porto Alegre. This dissertation explores the dynamics of functioning of the Municipal Council of Justice and Security of Porto Alegre in the year 2015, observed in its monthly meetings of that year. It can be said that the space model is adequate, but participation is very incipient, dependent on public management. As well as pointing out that, prior to the idea of how to think about public security policy, there is the reform and strengthening necessary for institutions, such as police. As a proposal of continuity of this study is the research of strategies of motivation between the residents and institutional representatives. Stimulating knowledge of their realities to align with political practice.